Elastase-Activated Antimicrobial Peptide for a Safer Pulmonary Treatment of Cystic Fibrosis Infections - Margherita Degasperi; Riccardo Sgarra; Mario Mardirossian; Sabrina Pacor; Massimo Maschio; Marco Scocchi (MDPI AG, 2022)
As bioactive small proteins with antimicrobial and immunomodulatory activities that are naturally produced by all living organisms, antimicrobial peptides (AMPs) have a marked potential as next-generation antibiotics. However, their development as antibacterial agents is limited by low stability and cytotoxicity. D-BMAP18, a membrane-permeabilizing antimicrobial peptide composed of D-amino acids, has shown good antibacterial and anti-inflammatory activities but also a non-negligible cytotoxicity against eukaryotic cell lines. In this study, a prodrug has been developed that extends the peptide with a negatively charged, inactivating sequence containing the cleavage site for neutrophil elastase (NE). The ultimate goal was to allow the activation of D-BMAP18 by endogenous elastase only at the site of infection/inflammation, enabling a slow and targeted release of the pharmacologically active peptide. In vitro activation of Pro-D-BMAP18 was confirmed using purified NE. Its antimicrobial and cytotoxic activities were tested in the presence and absence of elastase and compared to those of the parental form. The prodrug had minimal activity in the absence of elastase, while its proteolysis product retained an appreciable antimicrobial activity but lower cytotoxicity. Moreover, Pro-D-BMAP18 was found to be correctly converted to D-BMAP18 in the presence of CF sputum as a model of the lung environment and showed good antimicrobial activity under these conditions.